Os slogans na propaganda de medicamentos: um estudo transdisciplinar: comunicação, saúde e semiótica - Jesus, Paula Renata Camargo de (2008)
Studying slogans as advertising messages is a rather complex task, particularly medication slogans, which, in addition to seeking to be objective, concise, and persuasive characteristics that are peculiar to slogans , must also be concerned with the regulations that govern this type of advertisement in Brazil. This thesis proposes a transdisciplinary study of communications, health, and semiotics (with emphasis placed on Charles Sanders Peirce s semiotics). The research is based on the theoretical perspective built based on a set of conceptions found among authors who transit in these apparently distinct areas. Slogans were analyzed based on bibliographic research, in books and documents, in search of fundamental historical elements to understand how they are configured, their function, and trends in advertisements designed for medications marketed freely over means of mass communication, particularly billboards and external media, where they are propagated, even with legal restrictions. Additionally, they were also studied through professional opinion interviews, the purpose of which was hear several voices on the matter. The empirical research contributed to the Peircean semiotics analysis, via records of advertisement images presented in open air, in order to undertake the verbal and visual analyses as exhibited in the exterior media and in billboards. Finally, it is concluded that medication slogans inherit a language that appeals to salvation which was used by poets of past centuries and which, when currently inserted in certain contexts, such as in external media, is persuasive, although the slogans often disrespect the laws that govern medication-related advertisement in Brazil. Through verbal and visual complementarity, it is noticed that the slogans persuasive language is made legitimate when inserted in the means of mass communication